2012
DOI: 10.1007/s10238-012-0224-3
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the promoter regions of Foxp3 and ICOSLG genes are associated with Alopecia Areata

Abstract: Alopecia areata (AA), an autoimmune disease affecting anagen stage hair follicles, is associated with polymorphisms in immune-related genes and with decreased number of CD4? CD25? T regulatory cells (Treg). Treg function is modulated by the forkhead box protein 3 (FOXP3) transcription factor and by inducible costimulator (ICOS), through interaction with the relative ligand, ICOSLG, whose genes are polymorphic. The aim of the study was to investigate whether specific single nucleotide polymorphisms (SNPs) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…Although overall Foxp3 + Treg numbers seem to be normal in PBMC populations of AA patients, their function is impaired [99,118]. SNPs in the promoter regions of gene Foxp3 and gene ICOSLG (inducible T-cell co-stimulator ligand) which affects Treg functions have been associated with a reduced expression of the FOXP3 and ICOSLG genes in AA patients [119]. It has recently been shown that cutaneous memory Tregs (mTregs) reside in human skin which have unique cell surface marker expression and cytokine production [120].…”
Section: Deficient Function Of Regulatory T Cells In Alopecia Areatamentioning
confidence: 99%
“…Although overall Foxp3 + Treg numbers seem to be normal in PBMC populations of AA patients, their function is impaired [99,118]. SNPs in the promoter regions of gene Foxp3 and gene ICOSLG (inducible T-cell co-stimulator ligand) which affects Treg functions have been associated with a reduced expression of the FOXP3 and ICOSLG genes in AA patients [119]. It has recently been shown that cutaneous memory Tregs (mTregs) reside in human skin which have unique cell surface marker expression and cytokine production [120].…”
Section: Deficient Function Of Regulatory T Cells In Alopecia Areatamentioning
confidence: 99%
“…systemic lupus erythematosus, psoriasis and vitiligo. Moreover, the occurrence of this SNP has been shown, by other authors, to be associated with susceptibility to alopecia aerata [12]. It would be interesting to investigate in the near future the possible pathogenetic mechanisms underlying these skin-related autoimmune disorders.…”
Section: Discussionmentioning
confidence: 91%
“…rs2294020 has been investigated in juvenile idiopathic arthritis [10], hay fever [11], and alopecia areata [12]. In particular, Eastell et al [10], found no association between FOXP3 rs2294020 polymorphism and juvenile idiopathic arthritis in a case-control association analysis of a UK population, although the authors did not rule out FOXP3 as a candidate gene for this disease, due to the low statistical power obtained in male enrolled patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alopesi Areata (AA), değişik şekil ve büyüklükte olabilen, deride iz bırakmayan saç, kirpik, kaş, sakal, bıyık ya da vücudun diğer bölgelerindeki kılların yama biçimli dökülmesiyle karakterize otoimmün bir hastalıktır. AA her iki cinsiyeti de etkileyebilen bir hastalıktır ve dünya genelinde görülme sıklığı yaklaşık %1-2'dir [3]. AA'da saç kaybının olduğu alanlarda deri normal görünümdedir.…”
Section: Introductionunclassified